The Gulf War of 1991 Reconsidered - Bacevich, A. J.; Inbar, Efraim (BESA studies in international security, 2003)
The Gulf War of 1991 Reconsidered subjects one of the formative events of the post-Cold War era and a watershed in Middle Eastern international politics to a comprehensive reassessment. Condidering events from Arab, Israeli and American view points, the book examines the Gulf War's historical origins, conduct and legacy.